UCD sports engineering program - Jenkins, P. E.; Plaseied, A.; Khodaee, M. (Procedia Engineering, 2010)
The University of Colorado Denver (UCD) has taken the leadership role with the first Sports Engineering Program in the United States. Sports Engineering is an exciting new area of emphasis for graduate degrees in engineering. This educational program is offered through cooperation between the downtown Denver College of Engineering and Applied Science and the Anschutz Medical Campus, both part of the University of Colorado Denver. This program is showing great promise for high enrollments and exciting research opportunities working with the sports equipment manufacturers, the athletes, and the sports medicine community.